THE NATIONAL-AND-CULTURAL COMPONENT OF THE CONTENT OF TEACHING LITERARY READING AT ETHNIC MINORITIES SCHOOLS - Bohdanets-Biloskalenko, Natalia (Mountain School of Ukrainian Carpaty, 2018)
In today's realities of the social, cultural and educational space of Ukraine, it is important to create in children a national consciousness, a sense of patriotism. This is one of the major tasks of raising children and young people, as it provides for the cultivation of patriotic citizens of their country, capable of defending its independence and integrity. The modern school plays an important role in the formation of a person capable of taking an active part in all spheres of socio-cultural life of the country. The article substantiates the importance of the selection of texts of fiction on national and socio-cultural grounds in textbooks on literary reading for schools with a language of instruction of national minorities. The analysis of existing textbooks on literary reading for schools of national minorities is proposed. The author states that there are many ways of mastering the cultural experience of the Ukrainian people. However, the very artistic word has a tremendous impact on the small reader. Through the actions of heroes, historical, ethnographic, natural, cognitive texts, there is an acquaintance with the culture of the people, in which representatives of various national minorities live. As a result of the analysis and synthesis of various sources, the author states that works of national-cultural content play an important role in the formation of conscious citizens of their state. That is why textbooks for literary reading for junior pupils with language teaching in national minorities should be comprised in the overwhelming majority of these works. In the article the significance of selecting literary texts based upon national and socio-cultural principles for textbooks in literary reading for schools providing teaching in minority languages is elaborated. The analysis of the current textbooks in literary readings for schools for national minorities is accomplished.